DAMPAK PROGRAM EKOWISATA BERBASIS KEARIFAN LOKAL DALAM PENINGKATAN PENDAPATAN MASYARAKAT - Gabriela Paula; Achmadi Achmadi; Syamsuri Syamsuri (Laboratorium Jurusan Antropologi, Fakultas Ilmu Budaya, Universitas Halu Oleo, 2022)
The eco-tourism program benefits much the community, where social culture and local wisdom of the people in each of regions preserve their custom, culture and sustainability differently. This study aims to determine the role of community and the role of local wisdom, the inhibiting and supporting factors, as well as the impact of the ecotourism program based on local wisdom in increasing the people's income. The research method used was a case study with a qualitative research type. The data sources for this study consisted of key informants including the Head of Dusun (Hamlet) and the Head of the Kaban Mayas Tourism Management Group, as well as regular informants including 7 (seven) local people from the Meliau hamlet. The methods of collecting data used were in-depth interviews and observation. The result of this study reveals that the role of the community is very important because local knowledge they have can help the implementation of ecotourism, where the community contributes to providing homestay, consumption, transportation and local guide or porter services and the ecotourism program is regulated by customary rules living in the community. The factor inhibiting the ecotourism program is mainly related to access to transportation, while the factor supporting is related to natural potency, cultural potency, animal diversity, and public awareness. The ecotourism program in Meliau Hamlet has a positive impact on community income, because the community has additional sources of income from managing homestay services, transportation services, and local guides. In addition, it also has an impact on improving the quality of processed non-timber forest products so that they have a fairly high selling value and also helps the marketing process. The findings of this study is expected to be taken into account in formulating local government policies in supporting the participation of local communities in ecotourism areas so as to increase their income.